Infectious Etiologies of Parkinsonism: Pathomechanisms and Clinical Implications - Limphaibool, Nattakarn; Iwanowski, Piotr; Holstad, Marte Johanne Veilemand; Kobylarek, Dominik; Kozubski, Wojciech (Frontiers in Neurology, 2019)
Extensive research in recent decades has expanded our insights into the pathogenesis of Parkinson’s disease (PD), though the underlying cause remains incompletely understood. Neuroinflammation have become a point of interest in the interconnecting areas of neurodegeneration and infectious diseases. The hypothesis concerning an infectious origin in PD stems from the observation of Parkinson-like symptoms in individuals infected with the influenza virus who then developed encephalitis lethargica. The implications of infectious pathogens have later been studied in neuronal pathways leading to the development of parkinsonism and PD, through both a direct association and through synergistic effects of infectious pathogens in inducing neuroinflammation. This review explores the relationship between important infectious pathogens and parkinsonism, including symptoms of parkinsonism following infectious etiologies, infectious contributions to neuroinflammation and neurodegenerative processes associated with parkinsonism, and the epidemiologic correlations between infectious pathogens and idiopathic PD.